Assessing climate change exposure of rural fresh water and sanitation – A case study in Cangio district - Tuan Le , Ngoc; Hoang Tran, Xuan (Vietnam Journal of Science and Technology, 2018)
By index method associated with professional adjustment, analytic hierarchy process (AHP), data collection, and GIS methods, the study aimed to assess climate change (CC) exposure (E) of rural fresh water and sanitation (RFWS) via 7 indicator groups (including temperature, precipitation, wind, saltwater intrusion -SI, drought, riverbank landslide, and inundation), a case study in Can Gio district (Ho Chi Minh city) in the period of 2015-2025. Exposure indices to CC of RFWS in Can Gio district would be almost at medium-low levels (E = 33 – 53) and tend to increase gradually from the infield to riverside areas, from land to sea. The highest E distributed in Thanh An, Long Tau riverside, and Phu Loi island. Some locations, having low E index but located in residential areas with plenty of infrastructures, could be more vulnerable, such as Nha Be riverside (Binh Khanh), Dong Dinh outfall, Tac Suot wharf (in Mieu Nhi, Mieu Ba -Can Thanh town), and Soai Rap riverside (Ly Nhon), and thus need taking into concerns.